Edukacja ekologiczna w polskiej podstawie programowej - Kozłowska, Agnieszka (Rocznik Pedagogiczny, 2021)
The purpose of the study was an investigation on a content of the core curriculum in Poland, for kin- dergarten children (aged 3–6) and primary school students (aged 7–18), in reference to educational demands, created by the global ecological crisis. As a source of these demands, IPCC Assessments Reports on Climate Change and UN over-arching strategies for sustainability and environmental education were used, as well as the European Union green policies’ package (The European Green Deal). Poland, as a member of the EU and a party of the United Nations Framework Convention on Climate Change, is obliged to promote and implement “green” policies, through incorporation of them into national legislation and the state system of education. The analysis revealed in Polish core curriculum lack of content, connected with the global ecological crisis and climate change, as well as with strategies of combating them. This result shows a dramatic content gap in environmental education of Polish students, regardless the fact that ecol- ogy is a fundament of global and European developmental strategies. The responsibility for this situation is beard on decision makers for a state educational policy; in a context of Polish law, this is the Ministry of Education and the Minister for Education himself.